Potential cost savings associated with dose rounding antineoplastic monoclonal agents. (August 2015) - Francis, Sarah M; Heyliger, Alexander; Miyares, Marta A; Viera, Marcos
Purpose: This study explored the potential financial benefits associated with dose rounding three costly cancer agents: bevacizumab, trastuzumab, and cetuximab. Methods: Electronic chemotherapy health record software was queried to identify inpatient and outpatient use of bevacizumab, trastuzumab, and cetuximab. Available drug vial sizes were noted. Costs of actual doses prescribed were compared to theoretically reduced doses (5% and 10%) adjusted to the nearest vial size. Only doses resulting in a decrease in the number of vials qualified for dose rounding. New doses were analyzed for potential cost savings considering the percent-change from the original dose. All institutional review board procedures were followed. Results: In all, 425 doses of bevacizumab, trastuzumab, and cetuximab were identified. At a 5% dose reduction, 51 doses (12%) qualified for dose rounding, translating to a potential cost savings of 60, 648 (6, 188, 52, 640, and 1, 820, respectively). Although a 5% limit was set, the average change in dose did not exceed 2.5%. At a 10% dose reduction, 124 doses (29%) qualified for dose rounding, translating to a potential cost savings of 112, 585 (26, 520, 80, 605, and 5, 460, respectively). With the 10% dose reduction, the average change in dose did not surpass 6.1%. Projected annual savings were calculated as 181, 944 or 337, 755, depending on the rounding limit. Conclusion: Consultation with key physicians regarding the proposed percent reduction resulted in a 10% dose reduction for all cases when utilizing these three agents. Implementation of a dose rounding protocol for bevacizumab, trastuzumab, and cetuximab represents a potentially substantial cost savings at this institution.